Design and Implementation of Trajectory Planning Algorithm for UAV Borne Air-to-Surface Missile - Yang, Kai; Xu, Chen; Xu, Yan (Journal of physics. Conference series, 2021)
This paper firstly introduces the development of domestic UAV borne air-to-ground missile guidance control systems and summarizes the current and ongoing research on the trajectory design of airborne missiles for unmanned aerial vehicles. Secondly, it introduces the traditional single-mode guided unmanned aerial vehicle air-to-ground missile trajectory design schemes and the new trajectory planning schemes for multi-mode compound guidance unmanned aerial vehicle borne air-to-ground missile. Finally, through mathematical simulation, it shows the characteristics of different trajectory schemes in terms of range, relative launch altitude and off-boresight capability.